2019
DOI: 10.1002/osi2.1021
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of arginine formulation in oral health care products

Abstract: Arginine (Arg) is derived from dietary intake, body protein breakdown, and endogenous Arg production, and is also present in saliva. Arg has been introduced as an additive in toothpaste and other fluoride‐containing dental care products and is now being promoted as more efficacious than conventional fluoride‐only toothpaste for the prevention of dental caries. Arg inclusion in dentifrice could potentially inhibit oral biofilm formation and destabilize dental plaque. Arg is expected to inhibit oral biofilm form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“… 11 Fluoride does not prevent the first step in the caries process, that is, acid production by cariogenic bacteria. 12 Moreover, the actions of fluoride on acid-producing microbes may be diminishing due to the evolution of fluoride-resistant species. 9 Therefore, it is imperative to supplement fluoride dentifrice with other potent modifiers and develop new remineralization therapies to bridge the gap in caries management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Fluoride does not prevent the first step in the caries process, that is, acid production by cariogenic bacteria. 12 Moreover, the actions of fluoride on acid-producing microbes may be diminishing due to the evolution of fluoride-resistant species. 9 Therefore, it is imperative to supplement fluoride dentifrice with other potent modifiers and develop new remineralization therapies to bridge the gap in caries management.…”
Section: Introductionmentioning
confidence: 99%
“… 10 In several clinical studies, adding arginine to oral healthcare products containing fluoride has shown to reduce the onset and progression of caries and dentin hypersensitivity. 12 …”
Section: Introductionmentioning
confidence: 99%